PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD INPRES 3/77 BAJOE 1 KABUPATEN BONE - Rahmadani. R; Jafar, Muh.Idris; Asriadi, Asriadi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is an experimental study aimed at determining the effect of the TGT-type cooperative learning model on students' mathematical communication skills in Mathematics for grade V students at SD Inpres 3/77 Bajoe 1. The research design used is Pre-Experimental with a One-Group Pretest-Posttest Design. The population consists of all grade V students at SD Inpres 3/77 Bajoe 1, with a sample of 27 students selected using the saturated sampling technique. The data collection technique used is a test to assess students' mathematical communication skills before and after the treatment with the TGT-type cooperative learning model. The data analysis methods used are descriptive and inferential statistical analysis. Based on the results of descriptive statistical analysis, the pretest average was 41.48, while the posttest average was 81.48. The obtained data were then analyzed using a paired sample t-test with a significance level of 5%. The data analysis results showed a significant difference between the pretest and posttest averages of students' mathematical communication skills before and after using the TGT-type cooperative learning model, indicating that the TGT-type cooperative learning model has an effect on students' mathematical communication skills in Mathematics for grade V students at SD Inpres 3/77 Bajoe 1.